Rapid Evaluation of Mutant Exon-11 in c-kit in a Recurrent MCT Case Using CD117 Immunocytofluorescence, FACS-Cell Sorting, and PCR. (10th September 2013) - Ketpun, Dettachai; Sailasuta, Achariya; Piyaviriyakul, Prapruddee; Onlamoon, Nattawat; Pattanapanyasat, Kovit
Abstract : A 13-year-old, poodle-mixed, male dog was referred to the oncology unit in our faculty's small animal teaching hospital with the problem of rapid recurrent MCT. The owner and the veterinarian would like to use a tyrosine kinase inhibitor (TKI) for the dog. Therefore, fine-needle aspiration (FNA) was performed to collect the MCT cells and these cells were submitted to our laboratory for the detection of internal-tandem-duplicated (ITD) mutation of exon-11 in c-kit, prior to the treatment. The aim of this paper is to demonstrate the use of combinatorial protocol for the rapid evaluation of ITD mutation in MCT cells harvested by FNA. However, there was no ITD-mutant exon-11 that had been observed in this case.